Tingkat Fertilisasi dan Perkembangan Embrio Mencit yang Diberi Ekstrak Buah Merah - S Said; O P Astirin; S Wahyuningsih (Media Peternakan, 2011)
In the present study examined the influence of red fruit extract (RFE) on fertilization rate and development of mice embryos during the pre-implantation stage. The application of RFE dose 0 ml/head/day, 0.05 ml/head/day, and 0.1 ml/head/day for seven days were conducted to examine its influence at the level of fertilization, then the application of RFE was continued during 0-3 days stage of pregnancy (0 day of pregnancy is the formation of the vaginal plug). The super-ovulation of the white mice was done by injecting of 5 IU PMSG and hCG (48 hours after PMSG), folowed by mating the females with males with ratio 1:1. The single-cell-embryos were collected 20 hours after the injection of hCG. The eggs were then fixed and stained before examinating the normal fertilization of eggs (formation 2 pronucleus). The morula and blastocysts were collected 84 hours after injection of hCG. The influence of the RFE with dose 0.1 ml on normal fertilization rate (formation 2 PN), significantly higher (46.01%) compared with dose 0.05 ml (37.51%) and controlled (16.38%). However, the influence of RFE with dose of 0.05 ml and 0.1 ml on the growth of pre-implantation stage embryos may inhibit the growth of mice embryos during the pre-implantation stage in vivo.